Asymmetric co-integration analysis of exchange rates and crude oil prices: evidence from India - Ali, Hamisu Sadi; Abdullahi, Yakubu John; Zubairu, Abba Nuhu; Yusuf, Mohammed Alhaji (IJECM, 2016)
Using monthly data from January, 1980 to July 2013, the aim of the article is to find out whether there is cointegrating relationship between exchange rates and crude oil prices in India. The result indicates that there exists cointegration between the variables and speed of adjustment shows symmetric based on TAR model, while MTAR model exhibit asymmetric adjustment. The findings indicated that exchange rates have significant influence on crude oil prices in India and the adjustment to equilibrium when variables deviated is non-linear. The implication is that Indian policy makers should focus more on their exchange rates dynamics in line with the persistent rises of crude oil prices that affects other macroeconomic variables specifically exchange rates that have significant influence on international trade considering the relevance of India in the international export market.